DAMPAK PEMBELAJARAN DARING DI TENGAH PANDEMI COVID-19 PADA SISWA SD/MI: LITERATUR REVIEW - Erwinestri Hanidar Nur Afifi; Riska Dwi Safitri (Program Studi Pendidikan Guru Madrasah Ibtidaiyah Institut Agama Islam Negeri Sorong, 2020)
The purpose of this research is to find out and find information about the impact of online learning on SD/MI students. The study used the literature review method. The results showed that the learning process during the pandemic changed by using a remote network. This has an impact on teachers because they are less than optimal in providing learning materials and disrupting the learning process which causes the expected learning objectives to not be achieved. So that it makes the material incomplete and the use of learning media in online learning is not optimal. Students’ assessments are also hampered by mere cognitive assessments. Another impact is also felt by students where they feel that online learning makes them unable to study face-to-face with the teacher. Accustomed to studying with their friends while joking. Adapting to online learning certainly takes time for students. A gradual process is needed so that students are able to accept changes in the new learning system for them.